Jesus Christ the witness of history - Anderson, James Norman Dalrymple, Sir, 1908- (Leicester, UK IVP, 1985)
Includes bibliographical referenes and indexes.
1st ed 1969 under the title: Christianity : the witness of history
Keywords: Jesus Christ -- historicity; Jesus Christ -- person and offices; Apologetics -- 20th century